Genotypic variation in spike fertility traits and ovary size as determinants of floret and grain survival rate in wheat - Guo, Zifeng (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.